Effects of a Peer-Buddy Lunchtime Toothbrushing Program on Plaque Levels among Grade 5 and 6 Students in Nongyasai District, Suphanburi Province - Therdpattaweepong, Anirat (Journal of Public Health and Innovation, 2026)
This quasi-experimental research aimed to examine the effects of a Peer-Buddy Lunchtime Toothbrushing Program on dental plaque reduction among Grade 5 and 6 students in Nongyasai District, Suphanburi Province. Initial participants consisted of 60 students, equally divided into an experimental and a comparison group (n=30 each). The experimental group participated in the Peer-Buddy program, which involved student pairs inspecting each other’s teeth after brushing and recording the results in a daily logbook for two months, while the comparison group followed their regular school oral hygiene routine. Research instruments included a knowledge test, an attitude scale, and plaque assessment using the Simplified Oral Hygiene Index (OHI-S), specifically the Debris Index Simplified (DI-S). Data were analyzed using descriptive statistics, Paired Samples t-test, and Independent Samples t-test at a .05 significance level. Final analysis included 57 students (Experimental n=28, Comparison n=29). Post-intervention results indicated that the experimental group exhibited a significant reduction in mean plaque scores, dropping from 1.70 ± 0.50 at baseline to 0.88 ± 0.38 post-test (p < .001). Furthermore, the post-test plaque levels in the experimental group were significantly lower than those in the comparison group (1.14 ± 0.57, t = -2.01, p = .049). These findings suggest that the Peer-Buddy Lunchtime Toothbrushing Program is an effective intervention for reducing dental plaque and promoting better oral hygiene practices among primary school students.